Desain Unit Pengolahan Bioetanol untuk Petani di Desa Ngajum Kecamatan Sumber Pucung Kabupaten Malang - Guritno, Bambang; Argo, Bambang Dwi; Yulianingsih, Rini (Jurusan Teknik Mesin, Fakultas Teknik, Universitas Brawijaya, 2011)
The aim of the research is to develop bio-ethanol processing unit in small size using simple technology, which can be used by Cassava farmers in the village of Ngajum Sumber Pucung Malang. The capacity of Bioethanol processing unit provided is 100 liters/process which consists of sieve, cooker with cooling mash, fermenter, and distillation unit. Tests on several processing units give the following results: Sieve driven by 7.5 HP diesel engines. Sieve cylinder made of wood cylinder with 40 cm of diameter and 45 cm of length. Sieve has a capacity of 613 kg/h. Cooker tank made of stainless steel plate 4 mm and has dimensions 77 cm of diameter and 150 cm of height. There are 4 pieces of pipe stainless steel 6